Associations among pericolonic fat, visceral fat, and colorectal polyps on CT colonography. (31st December 2014) - Liu, Jiamin; Pattanaik, Sanket; Yao, Jianhua; Dwyer, Andrew J.; Pickhardt, Perry J.; Choi, J. Richard; Summers, Ronald M.
ABSTRACT Objective To determine the association between pericolonic fat and colorectal polyps using CT colonography (CTC). Methods A total of 1169 patients who underwent CTC and optical colonoscopy on the same day were assessed. Pericolonic fat was measured on CTC in a band surrounding the colon. Visceral adipose tissue volume was measured at the L2‐L3 levels. Student's t‐tests, odds ratio, logistic regression, binomial statistics, and weighted kappa were performed to ascertain associations with the incidence of colorectal polyps. Results Pericolonic fat volume fractions (PFVF) were 61.5 ± 11.0% versus 58.1 ± 11.5%, 61.6 ± 11.1% versus 58.7 ± 11.5%, and 62.4 ± 10.6% versus 58.8 ± 11.5% for patients with and without any polyps, adenomatous polyps, and hyperplastic polyps, respectively (P < 0.0001). Similar trends were observed when examining visceral fat volume fractions (VFVF). When patients were ordered by quintiles of PFVF or VFVF, there were 2.49‐, 2.19‐, and 2.39‐fold increases in odds ratio for the presence of any polyp, adenomatous polyps, or hyperplastic polyps from the first to the fifth quintile for PFVF and 1.92‐, 2.00‐, and 1.71‐fold increases in odds ratio for VFVF. Polyps tended to occur more commonly in parts of the colon that had more PFVF than the spatially adjusted average for patients in the highest quintile of VFVF. Conclusions Pericolonic fat accumulations, like visceral fat, are correlated with an increased risk of adenomatous and hyperplastic polyps.